Prevalence And Intensity Of Ascaris lumbricoides Infection In Children Of Oemasi Village, Kupang District, East Nusa Tenggara Province, Indonesia - Meliance Bria; Novian Agni Yudhaswara; Ni Made Susilawati (Science Midwifery, 2022)
Worm infection is one of the health problems in all tropical, countries including Indonesia. The most frequent helminthiasis is the infection caused by the Soil Transmitted Helminth. Primary school-age children are an age group that is susceptible to helminthiasis. Worm infections can cause a serious impact if left untreated with no clean and healthy lifesthyle. This study was conducted to determine the prevalence and intensity of Ascaris lumbricoides in children of Oemasi village, Nekamese Subdistrict, Kupang District, East Nusa Tenggara Province, followed by the characterization of subjects. The descriptive design with the cross- sectional study applied to this research. Research subjects were 112 children age 6-12 years old. The infection was diagnosed microscopically by the Katokatz method. Ascaris lumbricoides were the only species found infecting a total of 7 children (6.25%). The distribution of ascariasis was higher in females (4 or 57.1%) than in males (3 or 42.9%) with the intensity of Ascaris lumbricoides infection was categorized as mild.